2007
DOI: 10.1016/j.ymssp.2005.09.015
|View full text |Cite
|
Sign up to set email alerts
|

A comparative experimental study on the diagnostic and prognostic capabilities of acoustics emission, vibration and spectrometric oil analysis for spur gears

Abstract: Prognosis of gear life using the acoustic emission (AE) technique is relatively new in condition monitoring of rotating machinery. This paper describes an experimental investigation on spur gears in which natural pitting was allowed to occur. Throughout the test period, AE, vibration and spectrometric oil samples were monitored continuously in order to correlate and compare these techniques to natural life degradation of the gears. It was observed that based on the analysis of root mean square (rms) levels onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
125
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(128 citation statements)
references
References 14 publications
3
125
0
Order By: Relevance
“…The results showed that the AEbased approach was more reliable, robust and sensitive to the detection of defects than the vibration based monitoring scheme. Similar approach is presented by Tan et al [12]. In [13], Li and He presented a methodology for gear health monitoring in rotational machinery.…”
Section: Introductionmentioning
confidence: 87%
“…The results showed that the AEbased approach was more reliable, robust and sensitive to the detection of defects than the vibration based monitoring scheme. Similar approach is presented by Tan et al [12]. In [13], Li and He presented a methodology for gear health monitoring in rotational machinery.…”
Section: Introductionmentioning
confidence: 87%
“…Gear defects: (a) scuffing, 46 (b) pitting 60 and (c) crack. 32 under excessively high stresses; thus, excessive load can cause permanent deformations; the accumulated plastic deformation mechanism consists of low cycle fatigue (LCF).…”
Section: Gearsmentioning
confidence: 99%
“…Once some abnormalities are detected these components are classed as failing and so preventive maintenance is planned. 79,80 etc. are modules that collect condition monitoring signal from wind turbine controller and transmits it to remote locations where these signals are studied and failures are detected.…”
Section: Section a A1 Planning For A Cbm Maintenancementioning
confidence: 99%